Ubiquitin–Proteasome-Dependent Regulation of Bidirectional Communication between Plastids and the Nucleus - Hirosawa, Yoshihiro; Ito-Inaba, Yasuko; Inaba, Takehito (Frontiers in Plant Science, 2017)
Plastids are DNA-containing organelles and can have unique differentiation states depending on age, tissue and environment. Plastid biogenesis is optimized by bidirectional communication between plastids and the nucleus. Import of nuclear-encoded proteins into plastids serves as anterograde signals and vice versa, plastids themselves send retrograde signals to the nucleus, thereby controlling de novo synthesis of nuclear-encoded plastid proteins. Recently, it has become increasingly evident that the ubiquitin-proteasome system regulates both the import of anterograde plastid proteins and retrograde signaling from plastids to the nucleus. Targets of ubiquitin-proteasome regulation include unimported chloroplast precursor proteins in the cytosol, protein translocation machinery at the chloroplast surface, and transcription factors in the nucleus. This review will focus on the mechanism through which the ubiquitin-proteasome system optimizes plastid biogenesis and plant development through the regulation of nuclear–plastid interactions.